100 Deadly Skills : The SeaL Operative's Guide to Eluding Pursuers, Evading Capture, and Surviving any Dangerous Situation - Emerson, Clint (New York Touchstone, 2015)
Offers one hundred concise methods of surviving dangerous situations based on the skills of military special forces operatives, covering such topics as evading ambushes, escaping confinement, and winning a knife fight.
Include Index and Illustration
Keywords: Survival -- United States. Navy. SEALs -- Combat survival